Gender budgeting in OECD countries - Downes, Ronnie (OECD Publishing, 2017)
Gender gaps persist in education, employment, entrepreneurship and public life opportunities and outcomes. Gender budgeting involves using the tools, techniques and procedures of the budget cycle in a systematic way to promote equality. Responses to the 2016 OECD Survey of Gender Budgeting Practices show that almost half of OECD countries have introduced, plan to introduce or are actively considering the introduction of gender budgeting. The OECD analysis demonstrates that a wide variety of gender budgeting approaches are practised. Only half of OECD countries can currently point to specific examples of impact, however a wider range of impacts may become more evident in the future since the introduction of gender budgeting is relatively recent in many countries. Useful areas for further study and policy action include: the routine availability of gender-disaggregated data; embedding of genderspecific approaches within the normal annual routines of budgeting; and complementing executive-led approaches with external quality assurance. JEL codes:H54, H60, H61 Keywords: Gender budgeting, gender equality, budgetary process, budgeting practices